(untitled) (Analysis of International Sciences, 2023)
This article gives information about recent changes in the sphere of education system in Uzbekistan as well provides striking data about worldwide actions in order to improve dwellers` literacy. Views of researchers and scientists of the world and Uzbekistan are also given.